Portability of executable service-oriented processes: metrics and validation. Issue 4 (December 2016) - Lenhard, Jörg; Wirtz, Guido
Abstract A key promise of process languages based on open standards, such as theWeb Services Business Process Execution Language, is the avoidance of vendor lock-in through the portability of processes among runtime environments. Despite the fact that today various runtimes claim to support this language, every runtime implements a different subset, thus hampering portability and locking in their users. It is our intention to improve this situation by enabling the measurement of the portability of executable service-oriented processes. This helps developers to assess their implementations and to decide if it is feasible to invest in the effort of porting a process to another runtime. In this paper, we define several software quality metrics that quantify the degree of portability of an executable, service-oriented process from different viewpoints. When integrated into a development environment, such metrics can help to improve the portability of the outcome. We validate the metrics theoretically with respect to measurement theory and construct validity using two validation frameworks. The validation is complemented with an empirical evaluation of the metrics using a large set of processes coming from several process libraries.